Romeo and Juliet - Shakespeare, William, 1564-1616.; Crowther, John (John C.) (New York : Spark Pub., 2003)
Presents the original text of Shakespeare's play side by side with a modern version, with marginal notes and explanations and full descriptions of each character.
Keywords: Romeo -- (Fictitious character) -- Drama; Juliet -- (Fictitious character) -- Drama; Shakespeare, William, -- 1564-1616.; Conflict of generations -- Drama; Vendetta -- Drama; Young adult drama, English; Verona (Italy) -- Drama